Aerosolized Beractant in neonatal respiratory distress syndrome: A randomized fixed-dose parallel-arm phase II trial. (February 2021) - Sood, Beena G.; Thomas, Ronald; Delaney-Black, Virginia; Xin, Yuemin; Sharma, Amit; Chen, Xinguang
Abstract: Purpose: There is increasing research into novel techniques of administering surfactant to preterm infants (PTIs) with respiratory distress syndrome (RDS) receiving non-invasive respiratory support (NIRS). Although aerosolized surfactant (AS) is promising in PTIs receiving NIRS, the optimal surfactant dose and formulation, drug-device combination and patient profile is not known. The objective of this randomized clinical trial was to investigate the feasibility, safety, efficacy and impact of four dosing schedules of AS using two nebulizers in PTIs with RDS stratified by gestational age (GA). Methods: PTIs with RDS receiving pre-defined NIRS for ≤8 h were assigned to 4 A S dosing schedules and 2 nebulizers within three GA strata (I = 24 0/7 -28 6/7, II = 29 0/7 -32 6/7, III = 33 0/7 -36 6/7 weeks). There was no contemporaneous control group; at the recommendation of the Data Monitoring Committee, data was collected retrospectively for control infants. Results: Of 149 subjects that received AS, the median age at initiation of the 1st dose and duration was 5.5 and 2.4 h respectively. There were 29 infants in stratum I, and 60 each in strata II and III. Of infants <32 weeks GA, 94% received caffeine prior to AS. Fifteen infants (10%) required intubation within 72 h; the rates were not significantly different between GA strata, dosing schedules and nebulizers for infants who received aerosolized surfactant. Compared to retrospective controls, infants who received AS were less likely to need intubation within 72 h in both the intention-to-treat (32% vs. 11%) and the per-protocol (22% vs. 10%) analyses (p < 0.05) with GA stratum specific differences. AS was well tolerated by infants and clinical caregivers. Commonest adverse events included surfactant reflux from nose and mouth (18%), desaturations (11%), and increased secretions (7%). Conclusions: We have demonstrated the feasibility, absence of serious adverse events and short-term efficacy of four dosing schedules of AS in the largest Phase II clinical trial of PTIs 24–36 weeks' GA with RDS receiving NIRS (ClinicalTrials.gov NCT 02294630). The commonest adverse events noted were surfactant reflux and desaturations; no serious adverse effects were observed. Infants who received AS were less likely to receive intubation within 72 h compared to historical controls. AS is a promising new therapy for PTIs with RDS.